PERBANDINGAN KINERJA PEMBANGKIT LISTRIK TENAGA ANGIN DAN TENAGA SURYA DI KAWASAN PESISIR - Sapta Harianto Sinaga; Siti Anisah (CV. Hawari, 2025)
The increasing global energy demand demands the development of sustainable renewable energy sources. Indonesia has great potential in utilizing solar and wind energy, especially in coastal areas. This study compares the performance of Solar Power Plants (PLTS) and Wind Power Plants (PLTA) based on energy efficiency, stability of electricity supply, costs, and environmental impacts. The research method used is a quantitative approach with direct measurements of solar radiation intensity and wind speed. The results show that PLTA has a higher efficiency (35%) than PLTS (18%), but its electrical power is more volatile. PLTS is more stable and has lower investment and maintenance costs than PLTA. In terms of the environment, PLTA has the potential to cause disturbances, while PLTS poses challenges in managing solar panel waste. By considering all aspects, the combination of PLTS and PLTA in a hybrid system is the optimal solution to increase the efficiency and confidentiality of electricity supply in coastal areas